Physiological correspondence between different indexes of high-intensity endurance exercise in young male runners - Massini, D. A.; Caritá, R. A. C.; Almeida, T. A. F.; Macedo, A. G.; Hernández-Beltrán, V.; Gamonales, J. M.; Espada, M. C.; Pessôa Filho, D. M. (Sports, 2025)
Critical speed (CS), the respiratory compensation point (RCP), and the midpoint between gas exchange threshold and maxial oxygen uptake (VO2max) (i.e., 50%delta) have been considered indexes able to demarcate the boundary between the heavy and severe exercise domains. However, the agreement between these indexes—and therefore the validity of using them reciprocally—remains to be reported in running. The current study analyzed the agreement between RCP, 50%delta, and CS. Twelve young runners performed an incremental test to assess VO2max, RCP, and 50%delta, with CS estimated by the linear model of time-limited trials at 90, 95, and 110% of the speed corresponding to VO2max. One-way ANOVA showed no differences when comparing VO2 and running speed at CS vs. 50%delta vs. RCP (47.5 ± 4.4 vs. 46.6 ± 4.4 vs. 47.8 ± 4.5 mLO2·kg-1·min-1; and 13.9 ± 1.3 vs. 13.7 ± 1.3 vs. 14.0 ± 1.4 km·h-1; p > 0.05 for all comparisons). The bias for 50%delta vs. CS was -0.82 ± 1.55 mLO2·kg-1·min-1 and -0.23 ± 0.55 km·h-1, and for RCP vs. CS, it was 0.36 ± 1.21 mLO2·kg-1·min-1 and 0.05 ± 0.46 km·h-1. Therefore, the agreement between RCP, 50%delta, and CS in estimating VO2 responses and running speed did not preclude their reciprocal similarity in exercise intensity, although the observed individual variability in physiological variables is a constraint on considering these indexes interchangeable.